Metodologia para análise da dependabilidade de Smart Grids - Marques, Danielle Brito (2015)
Smart Grids are a new trend of electric power distribution, the future of current systems. These networks are continually being introduced in order to improve the reliability of systems, providing alternatives to energy supply and cost savings. Faced with increasing electric power grids complexity, the energy demand and the introduction of alternative sources to energy generation, all components of system require a fully integration in order to achieve high reliability and availability levels (dependability). The systematization of a Smart Grid from the Fault Tree formalism enable the quantitative evaluation of dependability of a specific scenario. In this work, a methodology for dependability evaluation of Smart Grids is proposed. A study of case is described in order to validate the proposal. With the use of this methodology, it is possible to estimate during the early design phase the reliability, availability of Smart Grid beyond to identify the critical points from the failure and repair distributions of components.